Dddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddd
Answer:
No solution
Step-by-step explanation:
6X - 3Y = -9--------------(1)
- 2 X +Y= 5---------------(2)
from equation two,
Y = 5+2X------------------(3)
substitute equation (3) into equation (1)
6X-3(5+2X)= -9
opening bracket
6X-15-6X= -9
6X- 6X = -9+15
0 = 6
<h2>therefore the answer is no solution</h2>
x - Ram's age now
Ram is half his father's age now, so his father's age is two times Ram's age:
2x - Ram's father age now
x - 10 - Ram's age ten years ago
2x - 10 - Ram's father age ten years ago
ten years ago he was one third his father's age so his father's age was three times Ram's age:
2x - 10 = 3•(x - 10)
2x - 10 = 3x - 30
-10 + 30 = 3x - 2x
20 = x
2x = 2•20 = 40
Answer:
<u>Ram is 20 years old now, Ram's father is 40 years old now.</u>
<h3>-25.5 < -20.5</h3>
Step-by-step explanation:
<h3>Hope it helps you !!!</h3>
148.57-94 would equal 54.57